Antioxidant Activity from Combination of Centella asiatica Herb Extract and Moringa oleifera Leaves Extract - Shelly Taurhesia; Ratna Djamil; Wahyuni Djoko (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2022)
Antioxidants have an important role in inhibiting free radicals, where free radicals can cause a hereditary disease. Natural medicines that are efficacious as an antioxidant are Gotu kola and kelor leaves. This study aimed to obtain the potential antioxidant compounds in Gotu kola herb extract, kelor leaves extract and the combination using the DPPH method. This research was started by extracting simplicia with 96% ethanol, followed by preparing combination of Gotu kola extract and moringa extract ratio (1:1), (1:2), (1:3), (2:1), (3:1) which was carried out at a concentration of 20, 40, 60, 80, and 100 µl/mL. Furthermore, the antioxidant activity was tested by UV Vis spectrophotometry. Results showed that the IC50 value for the Gotu kola herb extract was 76.66 ± 0.56. Kelor leaves extract 82.66 ± 2.32, a combination of Gotu kola: Moringa (1:1) 74.07 ± 1.16, a combination of Gotu kola: Moringa (1:2) 86.56 ± 1.11, a combination of Gotu kola: Moringa (1:3) 65.09 ± 3.03, a combination of Gotu kola: Moringa (2:1) 56.65 ± 1.61, a combination of Gotu kola: Moringa (3:1) 67.58 ± 2.77. The best potential antioxidant activity was showed in the combination of Gotu kola: Moringa (2:1).